2010
DOI: 10.3354/meps08504
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress and the fitness effects of Mpi genotypes in the acorn barnacle Semibalanus balanoides

Abstract: Balancing selection has been invoked to explain the apparent maintenance of polymorphisms at the mannose-6-phosphate isomerase (Mpi) and glucose-6-phosphate isomerase (Gpi) loci in a diverse array of organisms. However, in many cases the agents of selective stress and the grain size of environmental heterogeneity necessary to preserve genetic variation remain uncertain. In the barnacle Semibalanus balanoides, differing selection regimes have been proposed across the species' range. To test whether or not fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…However, due to the lack of genome information, we are unable to annotate the gene function of these loci. Despite this, our results are consistent with previous studies on invertebrates that intra-population variation in stress tolerance depends on genotype (Watt 1977;Flight et al 2010).…”
Section: Genetic Basis Of Differential Thermal Tolerancesupporting
confidence: 93%
“…However, due to the lack of genome information, we are unable to annotate the gene function of these loci. Despite this, our results are consistent with previous studies on invertebrates that intra-population variation in stress tolerance depends on genotype (Watt 1977;Flight et al 2010).…”
Section: Genetic Basis Of Differential Thermal Tolerancesupporting
confidence: 93%
“…This "mosaic" model of thermal stress provides a potential explanation for why Mpi zonation varies from site to site. In addition, our evidence suggests that zonation is a habitatspecific process emerging from the interaction of many ecological variables, as exemplified by the controlled experiments of Flight et al (24), which showed that mortality from thermal stress in barnacles is affected by osmotic stress.…”
Section: Discussionmentioning
confidence: 58%
“…Consequentially, the interaction of high planktonic gene flow, panmictic settlement (specifically for Mpi), and strong microhabitat selection presents an evolutionary problem for Mpi in barnacles: Beneficial alleles within one microhabitat may not become fixed because offspring are likely to settle into environments that drastically differ from their parents. As such, multiple authors have argued for a role of balancing selection as a multiple-niche polymorphism-sensu Levene (22)-as the mechanism for the maintenance of functional genetic variation at Mpi (8,15,23,24). While ecological and physiological evidence lends support to the hypothesis, a full molecular description of the locus is lacking.…”
Section: Significancementioning
confidence: 99%
“…Interestingly, populations south to the Miramichi River have a similar genetic composition to European populations at the Mpi and Gpi loci (Holm & Bourget 1994), an observation which could have filled in a secondary contact scenario. Mpi and Gpi may possibly be directly involved in the barrier (Flight et al. 2010) but irrespectively of the environment (i.e.…”
mentioning
confidence: 99%